Reproductive Physiology Modules (Out of Print) - Karen Marsh; Kyle Sliney; Andrew La Barbera (Association of American Medical Colleges, 2007)
Abstract This resource is a collection of six modules on reproductive physiology. Designed for first-year medical students, the modules are presented through video, animation, audio, graphics, and text. The modules cover steroid hormones, disorders of sexual differentiation, neuroendocrine control of reproduction, female reproduction, male reproduction, and fertilization. The modules were evaluated in a randomized crossover trial in the reproductive physiology block of the medical physiology course at the University of Cincinnati College of Medicine. Eighty-two students volunteered to participate in a randomized crossover trial of the learning modules in comparison with traditional lectures. The results indicated there were no statistical differences in performance on either the online quizzes or the examination between those students utilizing the module and those students attending the traditional lectures. Thus, we conclude that the independent, self-guided, interactive, web-based learning modules presented in this resource are just as effective as traditional lectures in teaching reproductive physiology to first-year medical students. Based on student feedback, we allowed for more advanced student control of the audio as well as reducing the amount of information presented per screen by breaking the information into smaller building blocks presented in separate modules.